Pendayagunaan Dana ZIS Pada Program Mahasiswa Cerdas Baznas (BAZIS) Provinsi DKI Jakarta - Sultan Antus Nasruddin Mohammad; Febriani Eka Maulida (Fakultas Syariah dan Ekonomi Islam Institut Ilmu Al-Qur'an (IIQ) Jakarta, 2020)
This study aims to analyze the management of the utilization of ZIS to improve education and analyze the mechanism of the utilization of ZIS funds in BAZNAS (Bazis) DKI Jakarta Province in the Smart Student Program (Program Mahasiswa Cerdas). The results of this study indicate that the Utilization of ZIS to improve education in BAZNAS (Bazis) of DKI Jakarta Province has been done well and optimally in accordance with zakat utilization standards, namely distribution is given to asnaf sabilillah specifically in the religious and poor sectors of the poor. By giving priority to people who are powerless to meet basic needs and then provide assistance to their education. In addition, the mechanism for the Utilization of ZIS in BAZNAS (Bazis) of DKI Jakarta Province in the Smart Student Program is implemented well and fairly in accordance with the zakat utilization standards in Indonesia.